Global Engagement Strategy Leadership Fund - Kassianos, Angelos P. (My University, 2026)
Received a Global Engagement Strategy Leadership Fund by the UCL Global Engagement Office for a study visit at Koc Medical School, Istanbul, Turkey. https://www.ucl.ac.uk/global/news/2017/apr/fostering-innovative-european-collaborations
Keywords: Education